Linking Penetrance and Transcription in DYT‐THAP1: Insights From a Human iPSC‐Derived Cortical Model. Issue 6 (6th February 2021) - Baumann, Hauke; Ott, Fabian; Weber, Joachim; Trilck‐Winkler, Michaela; Münchau, Alexander; Zittel, Simone; Kostić, Vladimir S.; Kaiser, Frank J.; Klein, Christine; Busch, Hauke; Seibler, Philip; Lohmann, Katja
Abstract: Background: The THAP1 gene encodes a transcription factor, and pathogenic variants cause a form of autosomal dominant, isolated dystonia (DYT‐THAP1) with reduced penetrance. Factors underlying both reduced penetrance and the disease mechanism of DYT‐THAP1 are largely unknown. Methods: We performed transcriptome analysis on 29 cortical neuronal precursors derived from human‐induced pluripotent stem cell lines generated from manifesting and nonmanifesting THAP1 mutation carriers and control individuals. Results: Whole transcriptome analysis showed a penetrance‐linked signature with expressional changes more pronounced in the group of manifesting (MMCs) than in nonmanifesting mutation carriers (NMCs) when compared to controls. A direct comparison of the transcriptomes in MMCs versus NMCs showed significant upregulation of the DRD4 gene in MMCs. A gene set enrichment analysis demonstrated alterations in various neurotransmitter release cycle pathways, extracellular matrix organization, and deoxyribonucleic acid methylation between MMCs and NMCs. When specifically considering transcription factors, the expression of YY1 and SIX2 differed in MMCs versus NMCs. Further, THAP1 was upregulated in the group of MMCs. Conclusions: To our knowledge, this is the first report systematically analyzing reduced penetrance in DYT‐THAP1 in a human model using transcriptomes. Our findings indicate that transcriptional alterations during cortical development influence DYT‐THAP1 pathogenesis and penetrance. We reinforce previously linked pathways including dopamine and eukaryotic translation initiation factor 2 alpha signaling in the pathogenesis of dystonia including DYT‐THAP1 and suggest extracellular matrix organization and deoxyribonucleic acid methylation as mediators of disease protection. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society